Characterization of Sn- and Zn-loaded MCM-41 catalysts for nopol synthesis (2009)
ABSTRACT: Several heterogeneous catalysts based on MCM-41 were synthesized either by chemical vapor deposition (CVD) or hydrothermally, i.e. adding SnCl4, SnCl2 or ZnCl2 as precursor salts into the MCM-41 synthesis gel. Synthesized materials were characterized by XRD, BET surface area, atomic absorption, UV–Vis, H2- TPR, NH3-TPD, TEM and pyridine-FTIR. Better textural properties and more reactive materials were obtained using tin salt precursors compared with ZnCl2. UV–Vis and TPR analyses of selected Sn–MCM-41 materials indicate that depending on the synthesis and pretreatment conditions several species may be formed: Sn4+ as Lewis acid sites of different coordination, SnO2 nanoparticles and bulk tin oxide species. The presence of SnO2 nanoparticles was also confirmed by TEM. Medium strength Lewis acid sites appear to increase nopol selectivity. Hydroxylated groups, i.e. Sn–OH, increased the weak acid sites and diminished nopol selectivity. Keywords: Nopol, Sn–MCM-41, Zn–MCM-41, CVD, Hydrothermal synthesis.